2023
DOI: 10.1057/s41599-023-02140-9
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge-based HRM and business process innovation in the hospitality industry

Muddassar Sarfraz,
Kausar Fiaz Khawaja,
Mahmoona Khalil
et al.

Abstract: This study examines the impact of knowledge-based HR practices on business process innovation under the moderating role of Knowledge-Centered Organizational Culture (KCOC) and the mediating role of Absorptive Capacity (AC). Data was collected from the managers of hospitality firms via questionnaires from May to September 2022, using a quantitative data analytic process. The results demonstrate that formal and informal knowledge-based HR practices are vital to achieving business innovation performance with inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 108 publications
0
2
0
Order By: Relevance
“…Moreover, innovation is a prime element driving knowledge-based behaviors [ 50 ]. Technological knowledge applied in the entrepreneurial setting guides the innovation process.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Moreover, innovation is a prime element driving knowledge-based behaviors [ 50 ]. Technological knowledge applied in the entrepreneurial setting guides the innovation process.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…The facilitator should not have totalitarian control over the participants and focus on the use of PowerPoint, yet change the training in other ways, for example, talking in a comfortable place, which will make people dare to speak more. After action review (AAR) with discussions after important activities, re cording suggestions, precautions, and knowledge gained from that task or using reflection techniques in exchanging new ideas and bringing them to a conclusion is collaborative learning (Sarfraz et al, 2023). In addition, Shahriar et al, (2023) suggested that the digital learning ecosystem offered flexibility in time, place, and pace, which provided essential convenience.…”
Section: Literature Reviewmentioning
confidence: 99%